(untitled) (Singaporean Journal of Business Economics and Management, 2017)
The modeling and documentation of the Business plan has been discussed in detail, by emphasizing the steps for optimizing the Administration’s Function, Process and Behavior. A new form of the Administrators Function has been given in the form - A.F.= f (d1,d2, d 3,....., d) where did,d,......,d, are the various duties being performed. This A.F. has to be maximized by any of the well-known techniques for the case under study. The importance of the equilibrium condition providing the maximum total output for the two markets together has been explained. The process for deriving this has been discussed for a fixed number of entrepreneurs N, and then computing the sum of the outputs. The administrator’s role of looking for the innovators for sustaining the growth of the organization, and also to try for its enhancement, has been emphasized. The new emerging model of administrator’s function has been explained by taking examples from the Industry.